Community’s Attitude and Behavior towards Food Waste Composting - ABDUL WAHAB, SITI HAJAR; MOHAMED YUSOP, FATIMAH; TUAN ISMAIL, TUAN NOOR HASANAH (Progress in Engineering Application and Technology, 2021)
Huge increases in the production of the food waste have a direct effect on human life. The separation sources method was established by reusing it as a feedstock for downstream treatment processes, including composting or anaerobic digestion, in order to minimize the amount of food waste sent to the landfill. However, these attempts only succeed with constructive public attitudes and actions towards the system. Thus, a social survey (using questionnaire) was conducted to examine the lifestyle of the population and influence factors against food waste in households. In November 2020, the questionnaire was conducted among 50 respondents in Malaysia, especially in the 20’s above. The survey found that 55% of respondents with low income with a high members in-house (more than five) discarded more food waste compared to 12% of respondents with high incomes with a high members in-house (more than five) discarded less food waste. Therefore, the observation of the respondents’ of the issue of the kitchen waste separation and composting revealed that 90.0% of respondents did not distinguish their food waste from other waste, while 84.0% of respondents had knowledge of the issue of composting. This showed that lifestyles affect the understanding of the public and the amount of food waste produced.